Primate FSH-receptor promoter nucleotide sequence heterogeneity affects FSH-receptor transcription - Brune, Maik; Adams, Christian Benjamin; Gromoll, Jörg (Molecular and cellular endocrinology, 2010)
Follicle-stimulating hormone (FSH) is essential for primate reproduction and acts via the FSH-receptor (FSHR). Although the FSHR expression is highly cell-specific, knowledge of the FSHR promoter and its transcriptional regulation is very limited. We applied a comparative genomic approach of important primate lineages to characterize the FSHR core promoter region. The core promoter sequences of the human and different primate species display significant variations in species-specific promoter activities shown by relative luciferase activity (RLA), ranging from 0.7-fold in the bonobo up to 3.5-fold in the chimpanzee compared to human. Comparison of the core promoter sequences revealed only very few interspecies nucleotide mismatches. Sequence homology ranged between 88% in the marmoset to 98% in chimpanzee compared to human FSHR. Mutagenesis of a single nucleotide next to a putative E-twenty-six (ETS) binding site caused a significant increase for human and a decrease for chimpanzee in RLA. An accompanying change in the pattern of protein binding to mutated human and chimpanzee ETS binding sites was demonstrated by EMSA, confirming a hitherto unknown role for this ETS binding site in FSHR promoter activity. Although the FSHR promoter displays a great sequence homology among primates, single nucleotide changes have significant impact on FSHR promoter activity. Thus promoter studies of closely related species could yield important insights into different regulatory promoter elements caused by nucleotide substitutions.